Ventilator-Associated Pneumonia in Children - O. I. Andriyanova; I. G. Khamin; Yu. A. Churlyaev; F. K. Manerov (Общая реаниматология, 2007)
Objective: to elucidate a role of the most significant risk factors in the development of outcomes of ventilator-associated pneumonia (VAP). Subjects and materials. In 1997—2006, the intensive care units of Novokuznetsk observed 77 children with VAP (a study group) and 30 patients without VANP who were on artificial ventilation (AV) for more than 2 days (a control group). In the group of VAP, there was a preponderance of babies of the first year of life (p=0.0097), children with the baseline pathology (p=0.0145), severe underlying diseases, multiply organ dysfunction (p=0.0388) who were long on AV. Sputum gram-negative microorganisms were shown to be isolated statistically significantly more frequently (p=0.0005). Conclusion. Antibacterial therapy should be started with a combination of reserve antibiotics by the de-escalation scheme. In children with VAP, the predictors of poor prognosis are a bilateral process; the preservation of fever in the patients on adequate antibacterial therapy and/or the preservation of the microorganism; a low (<300) oxygenation index; no positive X-ray changes. In VAP, attributive mortality was 10.4%. Key words: children, ventilator-associated pneumonia, risk factors, gram-negative microorganisms, oxygenation index, mortality.